Two years of sarilumab in patients with rheumatoid arthritis and an inadequate response to MTX: safety, efficacy and radiographic outcomes. (9th May 2018) - Genovese, Mark C; van Adelsberg, Janet; Fan, Chunpeng; Graham, Neil M H; van Hoogstraten, Hubert; Parrino, Janie; Mangan, Erin K; Spindler, Alberto; Huizinga, Tom W J; van der Heijde, Désirée; ,
Abstract: Objectives: To examine 2-year safety, efficacy and radiographic outcomes of sarilumab in adults with RA and inadequate response to MTX (MTX-IR). Methods: In the randomized, placebo-controlled MOBILITY trial, MTX-IR patients received subcutaneous sarilumab (150 or 200 mg) or placebo every 2 weeks (q2w) plus MTX for up to 1 year. Upon study completion, patients could enrol in the open-label, long-term extension study (EXTEND, NCT011046652), in which all patients received sarilumab 200 mg q2w plus MTX. Dose reduction to 150 mg q2w was allowed for abnormal laboratory findings and per investigator's discretion. Results: Of 1197 patients participating in MOBILITY, 901 entered EXTEND. Over the 2-year period, treatment-emergent adverse events (TEAEs) and serious AEs occurred at rates of 279.6 events per 100 patient-years and 16.6 events per 100 patient-years, respectively. The most common TEAEs were neutropenia, injection site erythema, increased alanine aminotransferase and upper respiratory tract infections. After 1 year in the open-label, long-term extension, disease activity reached similar levels regardless of initial treatment. Modified total Sharp scores at year 1 were maintained through year 2. Best radiographic outcomes were observed in patients initially randomized to sarilumab 200 mg q2w. After dose reduction, 89.4% of patients continued the study through 2 years. Conclusion: Sarilumab safety through year 2 was consistent with IL-6 receptor blockade. Clinical response was similar irrespective of initial treatment, and radiographic progression stabilized. Patients initiated on sarilumab 200 mg q2w had the best radiographic outcomes. Dose reduction allowed most patients to continue with the study.